Designing the Digital System Using SDLC Methodology to Increase Inspection Efficiency at PT. LV - Ahmad Tia Jafar; Andira Taslim; Athina Sakina Ratum (President University, 2023)
PT. LV is a manufacturing company focusing on precision plastic injection molding and electronic assembly. One of PT. LV manual systems is the Inspection Check Sheet (ICS). There is an indication of wrong decision-making regarding the inaccurate data of characteristics dimension of a part which causes the part to be detained. Based on the results of observations from June to August 2023. The number of inaccurate data at the ICS has 13 cases, with the total quantity of retained parts is 6496. There are several disadvantages if it is still done by manually. First, the average time consumed for the current system process takes 2 minutes and 45 seconds. Second, found seven unnecessary repetitive activities. Third, the approval process by Quality Control Supervisor takes once a week. Therefore, this study aims to design a digital ICS system using System Development Life Cycle methodology in order to make inspection check sheets more efficient. Then, the implementation of digital ICS system held from October to December 2022. In its implementation is successfully reducing the number of inaccurate data and retained part significantly to become 0 cases. The impact of designing digital ICS system reduces time consume 72,34% become 46 seconds. There are no more repetitive data input activities. Last, an approval process is done digitally using the digital ICS system.